2023
DOI: 10.3390/life13091873
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Neutrophil Gelatinase-Associated Lipocalin (NGAL) and Proprotein Convertase Subtilisin/Kexin Type 9 (PCSK9) for the Monitoring of Treatment Response to Cyclosporine in Patients with Psoriasis

Aleksandra Frątczak,
Bartosz Miziołek,
Agnieszka Łupicka-Słowik
et al.

Abstract: Neutrophil gelatinase-associated lipocalin (NGAL) may promote development of inflammation in psoriasis, whereas proprotein convertase subtilisin/kexin type 9 (PCSK9) may account for dyslipidemia in some psoriatic patients. The aim of the study was to analyze the influence of cyclosporine therapy on serum levels of NGAL and PCSK9 in patients with psoriasis vulgaris. Methods: Serum samples were obtained before and after three months cyclosporine therapy. Patients were grouped into responders and non-responders t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Its significance as a pivotal therapeutic target for hypercholesterolemia and coronary heart disease attenuation is evident [ 26 ]. A clinical study showed that the levels of PCSK9 in serum were moderately to severely correlated with the levels of LDL and total cholesterol (TChol) [ 27 ]. The FOURIER study demonstrated that PCSK9 inhibitors profoundly expunge LDL cholesterol from the circulatory system, leading to attenuated cardiovascular adversities [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Its significance as a pivotal therapeutic target for hypercholesterolemia and coronary heart disease attenuation is evident [ 26 ]. A clinical study showed that the levels of PCSK9 in serum were moderately to severely correlated with the levels of LDL and total cholesterol (TChol) [ 27 ]. The FOURIER study demonstrated that PCSK9 inhibitors profoundly expunge LDL cholesterol from the circulatory system, leading to attenuated cardiovascular adversities [ 28 ].…”
Section: Discussionmentioning
confidence: 99%